2016
DOI: 10.1111/aas.12833
|View full text |Cite
|
Sign up to set email alerts
|

No cases of perioperative allergy to local anaesthetics in the Danish Anaesthesia Allergy Centre

Abstract: None of the 162 patients with suspected perioperative allergic reactions and exposure to LA reacted on subcutaneous provocation with the relevant LA. Thus, no patients have been diagnosed with allergy to LA in DAAC in the period 2004-2013 and allergy to LA must be considered very rare in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 39 publications
0
19
1
1
Order By: Relevance
“…Despite their widespread use, IgE‐mediated hypersensitivity reactions to local anaesthetics are reported extremely rarely . A recent study confirms this in the perioperative setting …”
Section: Epidemiology and Important Causesmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite their widespread use, IgE‐mediated hypersensitivity reactions to local anaesthetics are reported extremely rarely . A recent study confirms this in the perioperative setting …”
Section: Epidemiology and Important Causesmentioning
confidence: 92%
“…In the highly specialized Danish Anaesthesia Allergy Centre, DPTs have been done routinely since 2004 with most drugs, when skin tests are negative, inconclusive or suspected to be false positive. 21,33,41,45,47,98 In smaller less specialized centres, it may be possible for allergists to collaborate with local anaesthetists about individual patients that might benefit from DPT with drugs used in the perioperative setting, after a careful risk-benefit evaluation.…”
Section: Drug Provocation Testing (Dpt)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important when the local anaesthetic is not the most suspected drug. 17,47 The survey showed that 10/13 ISPAR centres and 15/21 ANZAAG centres perform DPT with local anaesthetics.…”
Section: Local Anaestheticsmentioning
confidence: 99%
“…1 A Danish national survey over a 10-year period found that none of 162 patients with suspected perioperative hypersensitivity exposed to LAs had been diagnosed with true allergy. 9 Allergic reactions to LAs during anesthesia and surgery, especially anaphylaxis, can be life-threatening. It is a challenge for doctors to provide appropriate pain management for patients with true allergy to LAs.…”
Section: Introductionmentioning
confidence: 99%